👤

Prosiłbym o pomoc z tym zadaniem. Z góry dzięki!
Rozwiąż równania:
-x - 2 = -11
-5x +3 = -12
4x - 6 = 26
3x - 5 = 4 + 2x
7x + 14 = 5x -22
-5x + 12 + x = 2x - 12
2(x + 4) - 5(x + 3) =2
2(x- 3) + 3(4 - x) = 5
3(x- 4) -2(2x + 3) = -6


Odpowiedź :

-x - 2 = -11

-x=-11+2

-x=-9 |*(-1)

x=9

-5x +3 = -12

-5x=-12-3

-5x=-15 |:(-5)

x=3

4x - 6 = 26

4x=26+6

4x=32 |:4

x=8

3x - 5 = 4 + 2x

3x-2x=4+5

x=9

7x + 14 = 5x -22

7x-5x=-22-14

2x=-36 |:2

x=-18

-5x + 12 + x = 2x - 12

-5x-2x+x=-12-12

-6x=-24 |:(-6)

x=4

2(x + 4) - 5(x + 3) =2

2x+8-5x-15=2

-3x=2+15-8

-3x=9 |:(-3)

x=-3

2(x- 3) + 3(4 - x) = 5

2x-6+12-3x=5

-x=5-12+6

-x=-1 |:(-1)

x=1

3(x- 4) -2(2x + 3) = -6

3x-12-4x-6=-6

-x=-6+12+6

-x=12 |:(-1)

x=-12